The gene for the human immune interferon receptor is located on chromosome 6. - Rashidbaigi, A (1986)
When 32P-labeled human recombinant immune interferon gamma (Hu-[32P]IFN-gamma) is crosslinked to human cells with disuccinimidyl suberate, a complex with a molecular size of approximately equal to 117,000 Da was identified by sodium dodecyl sulfate/polyacrylamide gel electrophoresis. The formation of this complex is inhibited when the binding is performed in the presence of excess unlabeled Hu-IFN-gamma. The specific formation of the 117,000-Da complex is not observed in mouse L cells or Chinese hamster ovary cells. This complex shows all of the criteria that identify it as the Hu-IFN-gamma receptor or its binding subunit. The same complex can be formed following binding and covalent crosslinking of Hu-[32P]IFN-gamma to some hamster-human or mouse-human somatic cell hybrids. The presence of human chromosome 6 in the hybrids is necessary and sufficient for the formation of this complex. More specifically, the long arm of chromosome 6 seems sufficient. Therefore, we have localized the gene for the Hu-IFN-gamma receptor (or its binding subunit) to the long arm of human chromosome 6. The presence of this chromosome in the somatic cell hybrids is not adequate, however, to confer antiviral resistance to the hybrids in the presence of Hu-IFN-gamma.